Applied Computing and Information Technology - Lee, Roger; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book presents the scientific outcomes of the 6th International Conference on Applied Computing and Information Technology (ACIT 2018), which was held in Kunming, China on June 13-15, 2018. The aim of this conference was to bring together researchers and scientists, businessmen and entrepreneurs, teachers, engineers, computer users, and students to discuss the numerous fields of computer science and to share their experiences and exchange new ideas and information in a meaningful way. The book includes research findings on all aspects (theory, applications and tools) of computer and information science and discusses the practical challenges encountered and the solutions adopted to address them. The book features 13 of the conference's most promising papers.
SFactors Affecting Satisfaction of NCS Based Educational System -- Model-Driven Development of Mobile Applications Allowing Role-Driven Variants -- E-Learning Adaptation and Mobile Learning for Education -- Design and Evaluation of Soil pH IoT Sensor Attribute for Rice Agriculture in Central Africa -- A Study on the Architecture of Mixed Reality Application for Architectural Design Collaboration -- Exploring the Improvement of the Defense Information System -- A Modern Solution for Identifying, Monitoring, and Selecting Configurations for SSL/TLS Deployment -- Analyses of Characteristics of Changes in Cerebral Activation Status, Depending on Blood Types, in Response to Auditory Stimulation -- Development of Infant Care System Application.
Keywords: Computational intelligence; Artificial intelligence; Computational Intelligence; Artificial Intelligence